Comparative Evaluation of Scarification Techniques on Seed Germination and Seedling Performance of Lotus (Nelumbo nucifera) - M. Sainath Rao; M. Ramanjineyulu; C. T. Pratheeksha; G. C. Sravya (Public Health, 2026)
Seed propagation of Nelumbo nucifera is limited by strong physical dormancy due to its hard, impermeable seed coat. This study evaluated the efficacy of four scarification treatments-mechanical nicking, sand abrasion, hot water immersion and concentrated sulphuric acid (98%, 1 h)-compared with an untreated control, on germination, biochemical activity and early seedling growth under ambient conditions of Ananthapuramu, India (latitude 14°41′ N, longitude 77°36′ E) during June 2025. Scarification significantly enhanced imbibition, seed coat permeability, α-amylase activity, germination percentage and seedling vigour (p < 0.05). Among treatments, acid scarification was most effective, achieving 78.4% germination, the shortest mean germination time (4.6 days), highest enzymatic activity (5.76 μmol maltose min⁻¹ g⁻¹ FW) and superior seedling growth (plumule: 9.4 cm; radicle: 12.6 cm). Mechanical nicking and sand abrasion moderately improved germination, whereas hot water immersion showed limited effectiveness. Root-to-shoot ratios remained relatively stable across treatments, indicating balanced biomass allocation. These results demonstrate that optimised acid scarification efficiently overcomes physical dormancy, accelerates metabolic activation and enhances seedling establishment in N. nucifera, providing a reliable, cost-effective method for large-scale propagation and wetland restoration programs.